PENGARUH CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION PADA PAKET WISATA SEPEDA DI DESA PENGLIPURAN - Setyaningsih, Ni Wayan; Suardana, I Wayan; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Customer experience is one of the strategies created at the moment of truth that has a long-term impact on subsequent visiting decisions. Interest in revisiting in this study is called revisit intention, defined as the possibility of tourists to repeat activities or revisit a tourist attraction. This research was conducted to determine the effect of customer experience to the revisit intention of the domestic tourists of bicycle tour package users "Fun-Tastic Shuttle Bike Adventures" in Penglipuran Village. The technique of determining sample using purposive sampling technique by distributed 135 questionnaires to the domestic tourists who used bicycle tour packages "Fun-Tastic Shuttle Bike Adventures" as the respondents. Data collected by using questionnaires with Likert Scale and calibrated by using the validity test and reliability test to find coefficient Alpha Cronbach 0,6. The technique of data analysis used multiple linear regression analysis. Based on the calculation of PASW Statictic 18 (Powerful Statistic Software Application), the results indicate that there is no significant effect of customer experience to revisit intention on the bicycle tour package "Fun-Tastic Shuttle Bike Adventures" in Penglipuran Village.